Foundations of epistemology in early XXI century - Martínez Miguélez, Miguel (2010)
The realities of today’s world, both in its personal and family level, as in the social, political, religious and business one, have acquired, in the twentieth century, a high level of complexity. This calls, for its study and understanding, an interdisciplinary research approach, integrated and systemic, which, in turn, needs a consistent epistemological bases with its own special nature, because we live a radical transformation of the concept of knowledge and the concept of science, i.e., the criterion of scientific rationality. It will be fundamental objective of this study to clarify and illustrate that the problem lies in the restrictive concept of “scientificity” adopted, especially in the humanities, which cripples the legitimacy and right to exist of a wealth of more typical human endowment, as processes that are based on the use of freedom and creativity. Also, we will emphasize the need for a review of conceptual frameworks, theories and methods of philosophy of science involved, and seek to clarify the rationale and nature of the psychological mental processes that are implicit in it.